Significance of venous thromboembolism in women with uterine carcinosarcoma - Matsuo, Koji (Gynecol Oncol, 2017)
OBJECTIVE: To identify risk factors for venous thromboembolism (VTE) and to examine the association of VTE and survival in women with uterine carcinosarcoma. METHODS: This multicenter retrospective study examined 906 women who underwent primary surgical treatment for stage I-IV uterine carcinosarcoma. Time-dependent analyses were performed for cumulative incidence of VTE after surgery on multivariate models. RESULTS: There were 72 (7.9%) women who developed VTE after surgery with 1-, 2-, and 5-year cumulative incidences being 5.1%, 7.3%, and 10.2%, respectively. On multivariate analysis, older age (hazard ratio [HR] per year 1.03, P = 0.012), non-Asian race (HR 6.28, P< 0.001), large body habitus (HR per kg/m(2) 1.04, P = 0.014), residual disease at surgery (HR 3.04, P = 0.003), tumor size ≥5 cm (HR2.73, P = 0.003), and stage IV disease (HR2.12, P = 0.025) were independently associated with increased risk of developing VTE. A risk pattern analysis identified that obese Non-Asian women with large tumors (13.7% of population) had the highest incidence of VTE (2-year cumulative rate, 26.1%) whereas Asian women with no residual disease (47.1% of population) had the lowest (2-year cumulative rate, 1.6%) (P< 0.001). Presence of carcinoma/sarcoma in metastatic sites was significantly associated with increased risk of VTE compared to carcinoma alone (2-year rates, 31.2% versus 8.4%, P = 0.049). VTE was independently associated with decreased progression-free survival on multivariate models (5-year rates, 24.9% versus 47.2%, HR 1.46,95%CI 1.05–2.04, P = 0.026). CONCLUSION: Our study suggests that VTE represents a surrogate marker of aggressive tumor behavior and diminished patient condition in uterine carcinosarcoma; obese Non-Asian women with large tumors carry a disproportionally high risk of VTE, suggesting that long-term prophylaxis may benefit this population.